The modification of bitumen with reactive ethylene terpolymer, styrene butadiene styrene and variable amounts of ethylene vinyl acetate - Keyf, S. (SPRINGER, 2015)
In this article, 50/70 penetration graded TUPRAS bitumen was modified. Reactive elastomeric terpolymer (Elvaloy RET) from DuPont, ethylene vinyl acetate (EVA) and styrene butadiene styrene (SBS) polymers were used in the bitumen modification. Set hours of the tests were applied to samples taken from the obtained modified bitumen mixture, and 1 % reactive ethylene terpolymer, 1 % SBS and 0.5, 1, 1, 5, 2, and 2.5 % EVA (w/w) were added to the raw bitumen. Penetration, penetration index, softening point, ductility and % elastic recovery tests were performed with the modified bitumen and raw bitumen. The samples of raw bitumen and modified bitumen with 2 % RET, 1 % SBS and 1 % EVA were investigated by means of IR spectroscopy (FT-IR) and thermogravimetrical analysis/differential thermal analysis (TG/DTA). The raw bitumen was modified with RET, SBS and EVA, and it was determined that the penetration and ductility values were decreased while the penetration index, softening point and % elastic recovery were increased. The most important characteristics (such as softening point, penetration and % elastic recovery) of the new polymer-modified bitumen (NPMB) containing 2.5 % EVA, 1 % RET and 1 % SBS were compared with eight different types of polymer-modified bitumens in Turkey (TPMB). NPMB provided all the required parameters (softening point, penetration and % elastic recovery) for two different types of TPMBs (TPMB 70-16, TPMB 70-22).
Keywords: Polymer modification of bitumen; Reactive ethylene terpolymer; Ethylene vinyl acetate; Penetration; Softening point; POLYMER; MICROSTRUCTURE; COPOLYMER; BLENDS; Chemistry